Spillover effects of foreign hypermarkets on domestic suppliers in Malaysia - Kaliappan, Shivee Ranjanee; Alavi, Rokiah; Abdullah, Kalthom; Zakaullah, Muhammad Arif (Emerald Group Publishing Limited, 2009)
Since the mid-1990s, there has been a rapid expansion of large-scale foreign retailers in many countries across Southeast Asia, Central Europe and Latin America. This emerging trend has triggered a number of research interests on the issue of retail globalization. The research aims to consider the entry of foreign hypermarkets in Malaysia and their impact on the development and growth of domestic suppliers and manufacturers. This study uses both primary and secondary data. Secondary data were drawn from industry sources which included government departments, economic reports, retailing magazines and companies, web sites. Meanwhile, primary data are collected using mail survey questionnaire and face-to-face interviews. The findings of this study indicate that foreign hypermarkets play a very important role in the development and growth of the domestic suppliers via backward linkages. The main forms of linkages are product supply, informational linkages, assistance with inventory management, technical support and quality assurance and procurement systems. A majority of the firms indicated that they benefited substantially from the presence of foreign hypermarkets; however, they also face several challenges brought about by imposition of several unfair terms and procurement policy. The findings are largely derived from the experience encountered by domestic firms who participated in the survey. Thus, it is believed that their views could definitely help all the parties including the policymakers and researchers to better understand the impact of foreign hypermarkets on local businesses and take appropriate policy measures.